Tranexamic acid as an aid to reducing blood transfusion requirements in gastric and duodenal bleeding. - von Holstein, C C (1987)
A prospective randomised double blind study examined the effect of the antifibrinolytic drug tranexamic acid compared with placebo in 154 patients bleeding from verified benign lesions in the stomach or duodenum or both. Three out of 72 patients receiving tranexamic acid underwent emergency surgery compared with 15 out of 82 given placebo (p = 0.010). Nineteen patients receiving placebo rebled during their admission as compared with 10 in the active treatment group (p = 0.097). Blood transfusion requirements were significantly reduced by tranexamic acid (p = 0.018). Side effects occurred in six patients, of which an uncomplicated deep venous thrombosis was the most severe. Tranexamic acid reduces the blood transfusion requirement and need for emergency surgery in patients bleeding from a benign gastric or duodenal lesion.